Development of Angiosperm Plants Booklet as A Biology Learning Media for Tenth Grade of Senior High School Students - Zulfa, Fathin Amalia; Sulistiyawati, Sulistiyawati (Proceeding International Conference on Religion, Science and Education, 2025)
The research aims to develop angiosperms plant booklets in the Mount Tidar Botanical Garden as a medium for biological learning and to know the feasibility of angiosperms plant booklets in the Mount Tidar Botanical Garden as a medium for biological learning. Development research includes Research and Development (R&D) research using ADDIE development models limited to the Analysis, Design, and Development stages. Booklets were developed using Canva software. Booklets that have been developed are then validated using assessment instruments including validation angket sheets and student response sheets. Booklet assessment was carried out by 1 material expert, 1 media expert, 1 biology teacher, and 15 students in grade X MIPA MAN 1 Magelang. The results of the product validity test assessment by both materialists and media experts showed that the validation with percentage of product assessment was respectively scored at 87% and 96% with excellent categories so that the product was said to be viable. The results of the validity test assessment of biology teachers and students showed validity with the percentages of 93% and 88% indicating "very good" categories. Based on the research results, the angiosperms plant booklets in the Mount Tidar Botanical Garden are well-suited and practically used as a medium for biological studies.